Fetal limb soft tissue assessment for prediction of birth weight and umbilical cord blood analytes in gestational diabetes. (3rd September 2015) - Garcia‐Flores, Jose; Cruceyra, Mireia; Cañamares, Marina; Garicano, Ainhoa; Nieto, Olga; Lopez, Ana; Dorronsoro, Izaskun; Tamarit, Ines; Sainz De La Cuesta, Ricardo
Abstract: Objective: To evaluate the value of third trimester ultrasound (estimated fetal weight, cheek‐to‐cheek diameter, sectional Wharton's jelly area, sectional areas and fractional volumes in extremities) to predict birth weight and cord biochemical markers at birth (leptin, insulin, c‐peptide, IGF1, erythropoietin and ferritin) in diabetic pregnancies. Method: Prospective study in 49 patients with gestational diabetes. An ultrasound was performed between 32 and 34 weeks. Clinical data were collected, and a blood sample was obtained from cord after birth. ROC curve models were evaluated for 75 th and 90 th birth weight percentile. Univariate and multivariate models were used to assess the association between ultrasound and neonatal outcomes. Results: Sectional areas and fractional volumes showed significant differences and highest AUC values for predicting birth weight. A significant association was found for extremities measurements with total birth weight and its percentile. The only marker which showed a significant association to estimated fetal weight was erythropoietin. Sectional areas and fractional volumes related to cord leptin, erythropoietin, insulin and c‐peptide. Conclusion: Sectional areas and fractional volumes improve the predictive value of estimated fetal weight in diabetic pregnancies. They also show a predictive association to biochemical changes in cord (leptin, insulin and erythropoietin) related to increased adiposity and risk of fetal hypoxia. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? The estimation of fetal weight to predict fetal macrosomia in diabetic pregnancies by ultrasound has shown a low sensitivity and specificity in previous literature. What does this study add? Sectional areas and fractional volumes in fetal limbs improve the predictive value of estimated fetal weight in diabetic pregnancies. They also show a predictive association to biochemical changes in cord related to increased adiposity and risk of fetal hypoxia.